Guidelines for Tracheostomy From the Korean Bronchoesophagological Society - Korean Bronchoesophagological Society Guideline Task Force; Inn-Chul Nam; Yoo Seob Shin; Woo-Jin Jeong; Min Woo Park; Seong Yong Park; Chang Myeon Song; Young Chan Lee; Jae Hyun Jeon; Jongmin Lee; Chang Hyun Kang; Il-Seok Park; et al. (Clinical and Experimental Otorhinolaryngology, 2020)
The Korean Bronchoesophagological Society appointed a task force to develop a clinical practice guideline for tracheostomy. The task force conducted a systematic search of the Embase, Medline, Cochrane Library, and KoreaMed databases to identify relevant articles, using search terms selected according to key questions. Evidence-based recommendations for practice were ranked according to the American College of Physicians grading system. An external expert review and a Delphi questionnaire were conducted to reach a consensus regarding the recommendations. Accordingly, the committee developed 18 evidence-based recommendations, which are grouped into seven categories. These recommendations are intended to assist clinicians in performing tracheostomy and in the management of tracheostomized patients.